(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
This article examines the influence of beauty standards on consumer self-esteem and behavior, focusing on the manicure segment. It examines the historical and cultural aspects of beauty standards, as well as the role of mass media and social media in creating idealized images of nails and manicure styles. Particular attention is paid to the practical implications for consumers: their choice of shades, designs, and manicure techniques, their visits to beauty salons, and their adherence to fashion trends. The study’s findings demonstrate that beauty standards significantly shape manicure preferences and influence clients’ self-esteem, which is important to consider when developing marketing strategies and professional practices.